Lebanese pastor finds a loving home during Raton visit - Williams, Jess (Raton Range Raton, New Mexico, 1988)
Newspaper article Pastor John Sabbagh who visited Ratons First Presbyterian Church and loved Raton. he would love to make Raton his home in America.
Master list item #: 8
File location is in the Raton File Cabinet
Keywords: Sabbagh, John; Johnson, Bruce; Johnson, Laurie; First Presbyterian Church; Parish of North Lebanon; Syndod of the Southwest of the Presbyterian Church; Local History; Life and Customs; Churches; Christians; Community; Friendships; Pastor; Raton, New Mexico; Lebanon; United States; Albuquerque, New Mexico; Phoenix, Arizona